Glasses and glass Ceramics for medical applications - El-Meliegy, Emad (Springer New York, 2012)
Glass ceramics are a special group of materials in which a base glass can be crystallized under carefully controlled conditions, which in turn determine the properties of the material. These materials offer a wide range of physical and mechanical properties combining the distinctive characteristics of sintered ceramics and glasses. This book provides readers with an interest in medical ceramics with the ability to start making their own glasses and glass ceramics, together with an understanding of the various factors that control the final properties of these medical and dental materials. In addition, the authors describe various industrial problems with current, clinically-used medical glass ceramics and discuss appropriate scientific solutions. Glasses and Glass Ceramics for Medical Applications will appeal to a broad audience of biomaterials scientists, ceramists, and bioengineers, particularly those with an interest in orthopedic and dental applications, as well as scientists and engineers involved in the manufacture of glasses, glazes, enamels, and other glass coatings for the medical materials industry. The book will also be of interest to undergraduate and graduate students in materials engineering and dentistry, and is suitable for use in courses on medical and dental materials. Systematically and comprehensively introduces the science of medical glasses and glass ceramics, covering their design, development and manufacturing Presents the factors involved in the effective scaling of ceramic properties through easy explanations of the fundamentals of ceramic solids and practical examples Provides the reader with the ability to vary the constituent chemical elements of the glass, control nucleation and crystallization, and thus regulate the different ceramic properties Discusses the modification of the glass compositions to produce various crystalline mineral phases and consequently different types of glass ceramics with a wide variety of properties for biomedical applications Describes currently used medical ceramic systems and the scientific and technical problems encountered in their application